Foreshadowing the End in Beowulf. Issue 8 (17th November 2018) - Sebo, Erin
ABSTRACT: In this article, I will reconsider the function and meaning of three connected instances of the word fyren, 879a, 915b, and 1744b. Each occurs in a passage in which a character offers Beowulf advice by comparing him to either Sigemund or Heremod. In each case, the passage establishes a highly complex network of allusions which illuminates Beowulf's present and his future. In each, I argue, it is possible to read fyren as a pun which foreshadows his fiery end. Intriguingly, the advice offered to Beowulf proves irrelevant, as the foreshadowing indicates. So, why is so much space dedicated to it? I suggest the answer to the question has a profound bearing on how we read the significance of the poem's tragic ending.